The entrepreneurial state in China : real estate and commerce departments in reform era Tianjin - Duckett, Jane, 1964- (Routledge, 1998)
Jane Duckett describes in detail new state business activities in China and explains why they have appeared. Using research on the northern city of Tianjin during the 1990s, she argues that individual departments, within the Chinese state, are involved in the market economy through the establishment of their own businesses. The book demonstrates that many of these businesses are genuinely entrepreneurial in the sense of profit-seeking, risk-taking and productive, rather than rent-seeking, speculative or profiteering. This entrepreneurialism is an important new dimension of state activity in.
Keywords: Tianjin (China) -- Commercial policy.; Government business enterprises -- China -- Tianjin.; Government corporations -- China -- Tianjin.; Entrepreneurship -- China -- Tianjin.; Real estate management -- China -- Tianjin -- Case studies.; Entreprises publiques -- Chine -- Tianjin.; Entrepreneuriat -- Chine -- Tianjin.; Immeubles -- Gestion -- Chine -- Tianjin -- Études de cas.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Commercial policy; Government corporations; Entrepreneurship; Government business enterprises; Real estate management; China -- Tianjin; Economische hervormingen.; Ondernemerschap.; Onroerend-goedmarkt.; Samfundsvidenskab -- Økonomi.; Electronic books.; Case studies; Case studies.; Études de cas.